Guidelines for evaluation and treatment of lead poisoning of wild raptors. (14th May 2017) - Fallon, Jesse A.; Redig, Patrick; Miller, Tricia A.; Lanzone, Michael; Katzner, Todd
ABSTRACT: Lead poisoning is a threat to birds, particularly scavenging birds of prey. With the availability of portable lead‐testing kits, an increasing number of field researchers are testing wild‐caught birds, in situ, for lead poisoning. We describe guidelines for evaluation of lead toxicity in wild raptors by outlining field testing of blood‐lead concentrations, presenting criteria for removing a lead‐poisoned bird from the wild for treatment, and suggesting strategies for effective treatment of lead intoxicated raptors. Field testing of birds is most commonly accomplished via portable electrochemical analysis of blood; visual observation of condition alone may provide insufficient evidence upon which to make a decision about lead poisoning. Our intended audience is not only the avian research community, but also rehabilitation facilities that may receive apparently uninjured birds. Best practices suggest that birds whose blood‐lead levels are <40 μg/dL be released back to the wild as soon as possible after capture. The decision to release or treat birds with blood‐lead levels between 40 μg/dL and 60 μg/dL should be made based on the presence of clinical signs of poisoning and relevant biological characteristics (e.g., breeding status). Finally, birds with blood‐lead levels >60 μg/dL are potentially lethally poisoned and best served if removed from the wild for appropriate treatment at a licensed rehabilitation facility and later released. We present guidelines for decision‐making when treating lead poisoning of wild raptors. Future work based on experimental studies will clarify the role of lead poisoning for specific species and be important to refine these guidelines to improve effectiveness. © 2017 The Wildlife Society. Abstract : Lead poisoning is a threat to birds, and there is an increasing number of field researchers testing wild‐caught birds for lead poisoning. Here, we describe guidelines for evaluation of lead toxicity in wild raptors by outlining field testing of blood‐lead concentrations, presenting criteria for removing a lead‐poisoned bird from the wild for treatment, and suggesting strategies for effective treatment of lead intoxicated raptors.